Research activity and scientific creativity of Akseleu Seydimbek (historical analysis) - Seiitzhan, D.K. (Karagandy University of the name of acad. E.A. Buketov, 2025)
Akseleu Seidimbek made an invaluable contribution to the development of Kazakh literature and art, culture and spirituality, left a bright trace in the history of Kazakhstan. He researched the past of the Kazakh people, its history, traditions, culture, the formation of the Kazakh people as a nation. A. Seidimbek, studying ethnography of Kazakh people, revealed its spiritual world, left a bright trace in the literary and cultural life of Kazakhstan. Thus, undeniable is the fact that all scientific activity of Akseleu Seidimbek was directed to the study of historical roots of the Kazakh people and left a great inheritance for descendants in the form of manuscript works. The study of Akseleu Seydimbek’s works gives an opportunity to solve a number of problematic issues that concern modern society. At the forefront can be put forward the issue related to the upbringing of the younger generation. In this connection, in this article on the basis of factual material the main stages of life and activity of the prominent Kazakh publicist are considered, and a historiographical review of his main works is made. Historiographical analysis allowed to fully explore the personality of A. Seydimbek, to determine his activities in the history of Kazakhstan. In the article, relying on the scientific and cognitive views of Prof. Akseleu Seydimbek about oral historiography of Kazakhs and sources of genealogy, shows the historical consciousness and the peculiarities of the formation of the worldview of the Kazakhs.
Keywords: Akseleu Seidimbek; historical personalistics; culture; oral history; art; Kazakh literature; history of Kazakhstan; A. Seidimbek’s heritage